Pengembangan Aplikasi Kalkulator Multifungsi Menggunakan Flutter Framework - Febri Listiana Harahap; Richi Andrianto; Pebriana Panggabean; Putri Hanafia; Panusunan Panusunan; Mulia Garang (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
Flutter is an open-source user interface (UI) software development kit (SDK) created by Google, designed for building natively compiled applications for mobile, web, and desktop platforms from a single codebase. It employs the Dart programming language and provides a rich set of pre-built widgets, offering developers the flexibility to craft visually appealing and interactive user interfaces. This paper presents an overview of the Flutter framework, discussing its core features, architecture, and benefits. Flutter's "hot reload" feature allows for real-time code changes without the need for a full application restart, enabling faster development and experimentation. The framework's performance is optimized by leveraging Skia, a graphics engine for smooth rendering, resulting in fast and fluid UI experiences. The Flutter ecosystem encompasses a thriving community, extensive documentation, and a wide range of plugins that extend functionality and simplify integration with native platform features. Its cross-platform capabilities streamline the development process and reduce time-to-market, making it a popular choice among developers and businesses alike. The paper also highlights some potential challenges faced when adopting Flutter, such as platform-specific issues and limited native functionality access. However, the benefits of code reusability, fast development cycles, and consistent UI across platforms outweigh these challenges for many projects. Overall, Flutter has emerged as a robust and versatile framework for building high-performance applications across diverse platforms. Its continuous evolution, strong community support, and commitment from Google position it as a promising solution for modern app development in the rapidly evolving world of technology.